Penguatan Nilai Aqidah dan Akhlak Anak Usia Dini Melalui Pertunjukan Drama Islami: Studi Pengabdian di BA Aisyiyah Ngombakan, Sukoharjo - 'Ilmi Azizah, Annafi' Nurul; Pratama, Syafi Widiya; Rahmadani, Amelya Puspita; Aghaariid, Luthfi Haniifah; Sakina, Salma; Al- Fara, Nayla Jasmine; Berliana, Nuke Intan (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to instill and strengthen the values of faith and morals in early childhood through the media of Islamic drama performances entitled "Friendship Without Limits". Early childhood is in the golden phase of character development, so a fun and communicative approach is key in the process of value education. Islamic drama was chosen as a medium because it is able to convey moral and spiritual messages visually, emotionally, and interactively. This activity was carried out at BA Aisyiyah Ngombakan. The methods used include Activity Preparation, Initial Observation and Needs Identification, Drama Implementation / Performance, and Reflection and Evaluation. The results of the activity showed an increase in children's understanding of Islamic values such as honesty, helping each other, compassion, and maintaining friendship within the framework of correct faith. Drama performances have proven to be an effective medium in Islamic character education for early childhood that is fun and meaningful.